Institutional Convergence of Synergistic Strengths for Developing Women Agripreneurs - Rashmi Singh , M. S. Nain , J. P. Sharma , J. R. Mishra , Anjani Kumar; R. R. Burman (Indian Journal of Extension Education, 2014)
Aparadigm shift from agriculture being as a way of life for managing farm commercially on lines of an agribusiness is an essential pathway to revitalize Indian agriculture and to make farming a more attractive and profitable venture. Agripreneurship have the potential to contribute to a range of social and economic development. Agripreneurship has potential to generate growth, diversifying income, providing widespread employment and entrepreneurial opportunities in rural areas, though is an intricate process of mobilizing, stimulating needs, inculcating entrepreneurial competencies, facilitating linkages with other agencies, mentoring and hand holding. The study was conducted in Hapur district of Uttar Pradesh where three villages Lalpur, Shyampur and Kania-kalianpur were selected purposively being predominantly engaged in agriculture and having scope of agripreneurship development due to their proximity to National capital of Delhi. Ninety farm women, 30 each from three villages and 20 officials from institutions engaged in agripreneurship development in the area (three from all seven agencies) formed the sample size of the study. Farmers taking up entrepreneurial activities generally faced the problems in marketing of their products. Well developed effective linkages among all the stakeholders resulted in higher profits for producers and consolidated production sites for marketing and supply chain agencies. Several institutions engaged in agripreneurship development with respective strengths were found effective in synergizing actions and impacts by organizing interaction meets and focus group discussions to arrive at common programmes and activities in a collaborative manner.